PHYTOCHEMICAL SCREENING OF ARTOCARPUS HIRSUTUS AND ITS ANTIMICROBIAL POTENTIAL - K, Shanmugapriya; S, Akanya; B, Anderson Clinton; S, Berril Nanzy; Pr, Prakash; V, Suganya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In the present study, the effort was aimed to evaluate the phytochemical components, antioxidant activity, and antimicrobial activity of Artocarpus hirsutus fruit and leaf. Methods: Each plant materials were extracted with two suitable solvents such as acetone and ethanol. Then, the extracts were tested for the presence of active phytoconstituents and antimicrobial activity. Then, it was subjected to antimicrobial activity against fungal and bacterial strains. Results: The present study suggested that the selected plant extracts of A. hirsutus exhibit major phytoconstituents, such as alkaloids, glycosides, terpenoids, phenols, and saponins. Furthermore, the results showed that acetone fruit extract of A. hirsutus and ethanolic fruit extract of A. hirsutus exhibited significant antimicrobial activity with a maximum zone of inhibition against Staphylococcus aureus and Aspergillus tamarii. Conclusion: The present study also exhibited remarkable antimicrobial activity against all the test microorganisms due to the presence of major bioactive phytochemicals